2018
DOI: 10.3390/v10010030
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Virome Analysis of Culex Mosquitoes from Kenya and China

Abstract: Many blood-feeding arthropods are known vectors of viruses that are a source of unprecedented global health concern. Mosquitoes are an integral part of these arthropod vectors. Advancements in next-generation sequencing and bioinformatics has expanded our knowledge on the richness of viruses harbored by arthropods. In the present study, we applied a metagenomic approach to determine the intercontinental virome diversity of Culex quinquefasciatus and Culex tritaeniorhynchus in Kwale, Kenya and provinces of Hube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 63 publications
6
69
0
Order By: Relevance
“…Our result shows that the assay could detect representative BAV isolates either from group A, B or C with no cross-reactivity with other tested mosquito-borne viruses such as DENV, CHIKV, YFV, WNV and JEV. At the same time, the result for the RT-LAMP assay for field-collected mosquito samples was consistent with RT-PCR and previously reported metagenomic analysis data, the mosquito samples with abundant BAV reads in metagenomic analysis were detected positively by RT-LAMP (Atoni et al, 2018;Xia et al, 2018b). In addition, this assay is fast and convenient.…”
Section: Discussionsupporting
confidence: 88%
“…Our result shows that the assay could detect representative BAV isolates either from group A, B or C with no cross-reactivity with other tested mosquito-borne viruses such as DENV, CHIKV, YFV, WNV and JEV. At the same time, the result for the RT-LAMP assay for field-collected mosquito samples was consistent with RT-PCR and previously reported metagenomic analysis data, the mosquito samples with abundant BAV reads in metagenomic analysis were detected positively by RT-LAMP (Atoni et al, 2018;Xia et al, 2018b). In addition, this assay is fast and convenient.…”
Section: Discussionsupporting
confidence: 88%
“…The presence in this study of such a large number of novel and unclassified virus assemblies highlights the fact that the malaria vector virome is understudied. The same observation has been made during metagenomics surveys in Drosophila , Aedes and Culex [24, 35, 36] among other arthropods, indicating that the vast majority of insect viruses are not yet discovered.…”
Section: Discussionsupporting
confidence: 64%
“…Since we could not sequence the honey used to impregnate the FTA cards as sugar bait, we cannot discard the possibility that these sequences might have come from it. However, recent virome studies have described these two families as the most abundant in culicid mosquitoes from the Yunnan province in China, and Zambezi province in Mozambique [49,50]. The additional description of honeybee-infecting virus Rhopalosiphum padi virus (Dicistroviridae, genus Cripavirus) in mosquito species from Hubei, China [51] and in Culex mosquitoes from California [41], together with the assembly of sequences linked to chronic bee paralysis virus (CBPV) (unclassified ssRNA+ virus) and Apis mellifera filamentous virus (dsDNA Hytrosaviridae family) from French Anopheles maculipennis [52] and from Culex mosquitoes from California [41] respectively, suggested that these viral families could be associated to mosquitoes as well.…”
Section: Virome Composition On Honey-baited Fta Cards During Entomolomentioning
confidence: 99%
“…Besides invertebrate-related viruses, it was not surprising to find viral families usually detected in plants, fungi and algae (e.g., Tymoviridae, Totiviridae, Partitiviridae, Endornaviridae or Virgaviridae) as part of the viral diversity associated to honey-baited FTA cards ( Figure 1B). Since, in Culex mosquitoes, sequences related to Totiviridae-like viruses have been found in Guadeloupe [46], Australia [25], China [49] and California [41]; Partitiviridae-like viruses have been detected in Sweden [45,48], Australia [25], Kenya [49] and California [41]; Endornaviridae-like viruses in Australia [25] and Tymoviridae-like viruses have been identified in Guadeloupe [46], Kenya [49], California [41], China [53], and Sweden [48]. Moreover, a Culex Tymoviridae-like virus (CuTLV) that was isolated from a Culex spp.…”
Section: Virome Composition On Honey-baited Fta Cards During Entomolomentioning
confidence: 99%